2002
DOI: 10.1590/s1517-83822002000100004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fungi growth and aflatoxin production with ergosterol content of corn grains

Abstract: The relationships between fungal growth and ergosterol content and between aflatoxins B1 and B2 production and ergosterol content were verified in corn grains. In the first experiment, fungal growth and ergosterol content were monitored during incubation of corn grains presenting water activities of 0.85aw and 0.92aw at 25ºC over a period of 18 days. For the Taiúba variety, the fungi growth and ergosterol content increased more rapidly for 0.92aw than 0.85aw. Maximum ergosterol levels were 2.8 and 4.6 µg/g, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…A significant correlation between ergosterol and aflatoxin contents during the incubation period was reported (Gourama and Bullerman 1995b;Castro et al 2002). The results of this study suggest that this correlation could be observed not only during incubation but also in products on/in which fungal growth had occurred.…”
Section: Resultssupporting
confidence: 50%
“…A significant correlation between ergosterol and aflatoxin contents during the incubation period was reported (Gourama and Bullerman 1995b;Castro et al 2002). The results of this study suggest that this correlation could be observed not only during incubation but also in products on/in which fungal growth had occurred.…”
Section: Resultssupporting
confidence: 50%
“…Results for a w values varied between 0.54 and 0.64, which is below the optimum level for fungal growth [23] . Ash content values varied between 0.97 and 1.35g/g.…”
Section: Maize Grain Characterizationmentioning
confidence: 93%
“…Litter was homogenized using a Tissue Tearor (BioSpec Products, Inc., Barlesville, OK). To determine total growth of each species on litter over time, we quantified ergosterol in each sample as an estimate of fungal cell growth and activity (Bååth, 2001;Castro et al, 2002). Ergosterol analysis followed the procedure of Montgomery et al (2000).…”
Section: Fungal Biomass and Enzyme Activity Analysesmentioning
confidence: 99%